Characterization of the Genital Microenvironment of Female Rhesus Macaques Prior to and After SIV Infection. (20th August 2015) - Nichols, Whitney A.; Birke, Leslie; Dufour, Jason; Loganantharaj, Nisha; Bagby, Gregory J.; Nelson, Steve; Molina, Patricia E.; Amedee, Angela M.
Abstract : Problem: HIV infection among women is frequently modeled in female rhesus macaques. Longitudinal studies on genital compartment and hormonal factors that can influence susceptibility to SIV infection are lacking in this animal model. Method of study: Genital specimens and menstruation of indoor‐housed female rhesus macaques were analyzed prior to and after SIV infection. Results: Median menstrual cycle length averaged 27 days, although highly variable cycle lengths and frequent periods of amenorrhea were observed during summer months. The vaginal microbiota, characterized by adapted Nugent scoring, showed predominance of small Gram‐variable rods and Gram‐positive cocci. Highly variable vaginal cytokine levels were observed pre‐ and post‐SIV infection. Vaginal viral loads correlated with plasma viral loads, but were not associated with progesterone levels. Conclusion: These results provide an integrated characterization of important factors in the vaginal microenvironment that are relevant to the experimental design of HIV prevention and transmission studies in female rhesus macaques.